Defining the Genome Features of Escherichia albertii, an Emerging Enteropathogen Closely Related to Escherichia coli. (3rd November 2015) - Ooka, Tadasuke; Ogura, Yoshitoshi; Katsura, Keisuke; Seto, Kazuko; Kobayashi, Hideki; Kawano, Kimiko; Tokuoka, Eisuke; Furukawa, Masato; Harada, Seiya; Yoshino, Shuji; Seto, Junji; Ikeda, Tetsuya; et al.
Abstract: Escherichia albertii is a recently recognized close relative of Escherichia coli . This emerging enteropathogen possesses a type III secretion system (T3SS) encoded by the locus of enterocyte effacement, similar to enteropathogenic and enterohemorrhagic E. coli (EPEC and EHEC). Shiga toxin-producing strains have also been identified. The genomic features of E. albertii, particularly differences from other Escherichia species, have not yet been well clarified. Here, we sequenced the genome of 29 E. albertii strains (3 complete and 26 draft sequences) isolated from multiple sources and performed intraspecies and intragenus genomic comparisons. The sizes of the E. albertii genomes range from 4.5 to 5.1 Mb, smaller than those of E. coli strains. Intraspecies genomic comparisons identified five phylogroups of E. albertii . Intragenus genomic comparison revealed that the possible core genome of E. albertii comprises 3, 250 genes, whereas that of the genus Escherichia comprises 1, 345 genes. Our analysis further revealed several unique or notable genetic features of E. albertii, including those responsible for known biochemical features and virulence factors and a possibly active second T3SS known as ETT2 ( E. coli T3SS 2) that is inactivated in E. coli . Although this organism has been observed to be nonmotile in vitro, genes for flagellar biosynthesis are fully conserved; chemotaxis-related genes have been selectively deleted. Based on these results, we have developed a nested polymerase chain reaction system to directly detect E. albertii . Our data define the genomic features of E. albertii and provide a valuable basis for future studies of this important emerging enteropathogen.